The obstacles facing women in balancing between work and home and its relationship to marital compatibility - Jameela Younis Sulaiman; Muhammad S. Al-Brwari (مجلة الآداب, 2023)
This research aims to identify the obstacles that women face in the balance between work and family and their relationship to marital compatibility in the center of Duhok city, through the answer to the research questions which are represented for knowing the most prominent obstacles and the level of marriage compatibility also the nature of the relationship between the obstacles and the marital compatibility, the researcher dependent to the descriptive analytic method to gain the answers for the research questions , the sample size of the research was (376) units  in the age between (23 to 61) from married female employees in government departments in the center of Duhok City, the tool of the research have two scale , first scale about women's work built by a researcher which include (58) questions  in three dimensions, which is (the obstacles facing women in social dimension, the obstacles facing women in psychological dimension, the obstacles facing women in economical dimension), also the researcher adopted a scale from the (Asma Ibrahim's PhD thesis in the title (occupational pressures and their relationship to marital compatibility among working women), the most important findings of the research it show that there is negative relationship between the obstacles that face women's work and their marital adjustment.